3D variability analysis: Resolving continuous flexibility and discrete heterogeneity from single particle cryo-EM - Punjani, Ali; Fleet, David J. (Journal of structural biology, 2021)
[Display omitted] •Continuous structural heterogeneity of proteins is often functionally relevant.•Existing single particle cryo-EM reconstruction algorithms yield static structures.•Algorithm that fits linear subspace model at high resolution is introduced.•New method resolves detailed molecular flexibility from single particle data. Single particle cryo-EM excels in determining static structures of protein molecules, but existing 3D reconstruction methods have been ineffective in modelling flexible proteins. We introduce 3D variability analysis (3DVA), an algorithm that fits a linear subspace model of conformational change to cryo-EM data at high resolution. 3DVA enables the resolution and visualization of detailed molecular motions of both large and small proteins, revealing new biological insight from single particle cryo-EM data. Experimental results demonstrate the ability of 3DVA to resolve multiple flexible motions of α-helices in the sub-50 kDa transmembrane domain of a GPCR complex, bending modes of a sodium ion channel, five types of symmetric and symmetry-breaking flexibility in a proteasome, large motions in a spliceosome complex, and discrete conformational states of a ribosome assembly. 3DVA is implemented in the cryoSPARC software package.